2017
DOI: 10.4300/jgme-d-16-00055.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2003 ACGME Resident Duty Hour Reform on Hospital-Acquired Conditions: A National Retrospective Analysis

Abstract: Background The Accreditation Council for Graduate Medical Education reforms in 2003 instituted an 80-hour weekly limit for resident physicians. Critics argue that these restrictions have increased handoffs among residents and the potential for a decline in patient safety. ''Never events'' hospital-acquired conditions (HACs) are a set of preventable events used as a quality metric in hospital safety analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been 20 years since the NQF published the first list of NEs. After two decades we have failed to eliminate these events and in some cases the incidence has increased 30 62 90 131 229 241 288 310 315 326 362 369. The lack of consensus in NEs, reporting structures, terminology and preventability impedes our ability to learn from each other and collaborate to reduce their occurrence.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Conversely, a systematic review conducted in 2014 on surgical residents revealed a potential escalation in complications and even increasing mortality as well 53 . In 2017, a large cohort study documented 110 million hospitalizations before and after the enforcement of the 2003 WHRs and showed that inpatient complications surged, particularly in teaching hospitals, with a reported increase of 10% 54 . A study comparing surgical patients before and after 2003 WHRs found a significant reduction in provider‐related complications (48% vs. 39%) 55 …”
Section: Work Hour and Related Outcomesmentioning
confidence: 99%